The Effect of Using Word Card Media on Beginning Reading Skills of Grade I Students of SD Inpres Barombong II, Tamalate District, Makassar City - Sarah Sulastri; Muhammad Irfan; Andi Dewi Riang Tati (International Journal of Elementary School Teacher, 2023)
This research uses a quantitative approach with the type of experimental research in the form of Quasi Experimental Design. This study aims to: (1) find out the description of the use of word cards in class 1 of SD Inpres Barombong II, Tamalate District, Makassar City, (2) find out how to describe initial reading skills using Word Card media for grade 1 SD Inpres Barombong II, Tamalate District. Makassar City, (3) found a significant effect of the use of word card media on the beginning reading skills of grade 1 Inpres Barombong II Elementary School, Tamalate District, Makassar City. The independent variable in this study was word card media while the dependent variable was reading skills. The population in this study were all grade 1 students of SD Inpres Barombong II, Tamalate District, Makassar City totaling 2 classes of 38 students, while the sample was class I A students totaling 21 students as an experimental class, then class IB as a control class totaling 17 students. The data collection technique used in this study was observation of the implementation of the learning process, reading tests were carried out twice, namely pretest and posttest and documentation in the form of learning tools and research documents. Research data analysis techniques using descriptive and inferential statistical analysis. Based on the results of the descriptive statistical analysis, it showed that the reading skills of the experimental class students differed from those of the control class. So it can be concluded that there is an effect of using word card media on students' initial reading skills. This is proven because there is a significant difference between the experimental class using word card media and the control class that does not use word card media.